Study on organic-dye sensitized photoelectrochemical solar cells - Sardar, Alam (My University, 2011)
The solar cell is one of the best conversion devices for future energy requirement because it has no hazards as compared to other energy sources. The dye-sensitized solar cell (DSSC) is a favourable, efficient, cheap device to convert solar energy. The dye is a key factor, responsible for the capturing of sunlight. This work is about the assembly of a DSSC with an organic dye and a PAN based gel electrolyte. The performance of the cells and of the electrolytes has been investigated with the help of complex impedance spectroscopy, DSC, and current/voltage characterization. The conductivity for the tetrahexlyammonioum iodide based gel electrolyte was 5.160×10-3 S/cm at 40 °C. The short circuit current and open circuit voltage of the cell with 1 kW/m2 light intensity and stabilized SQ2 dye using TiO2 substrate spin coated at 2500 rpm was 410 μA and 622 mV. The fill factor and the efficiency were 53.2 % and 0.081 % respectively. As a comparison, the performance of the cell based on a natural dye extracted from black rice was also measured. The open circuit voltage and short circuit current of this cell, under the illumination of 1kW/m2 were 410 mV and 503 μA. The fill factor and efficiency were 47.14 % and 0.057 %.
Keywords: Fysik; Physical Sciences